Sosialisasi Pemasaran Digital Untuk Meningkatkan Penjualan Pada Ibu Ibu Kelurahan Curug Bojongsari Depok - Laura Komala; Pusporini Palupi Jamaludin; Elizabeth Tika Kristina; Paringsih Paringsih (Institut Nalanda, 2024)
The aim of the Community Service Activities is to carry out one of the Tri Darmas of Higher Education which is carried out by lecturers and students at Pamulang University with the title